Metal-organic frameworks as kinetic modulators for branched selectivity in hydroformylation - Gerald Bauer (Nature Portfolio, 2020)
The Co-catalysed hydroformylation of olefins produces selectively linear but not branched aldehydes. Here, the authors show that microporous MOFs increase the olefins density in the pores beyond neat conditions allowing high branched selectivity through kinetic modulation when added to a liquid phase hydroformylation mixture.